Ion‐Exchange Strategy for Metal‐Organic Frameworks‐Derived Composites with Tunable Hollow Porous and Microwave Absorption (Small Methods 9/2022). Issue 9 (19th September 2022) - Tao, Jiaqi; Tan, Ruiyang; Xu, Linling; Zhou, Jintang; Yao, Zhengjun; Lei, Yiming; Chen, Ping; Li, Zhong; Ou, Jian Zhen
Abstract : Front Cover In article number 2200429, Zhou, Li, Ou, and co‐workers developed a universal ion‐exchange and in‐situ pyrolysis strategy to co‐regulate structural morphologies and chemical contents of metal‐organic framework derivatives, achieving enhanced microwave absorption performances.